Indirect Perpetration Theory: A Defence. (30th October 2015) - GRANIK, MARIA
Abstract: The aim of this article is to show that the concept of perpetration by means as it appears in Article 25 of the Rome Statute of the International Criminal Court (Rome Statute) accurately reflects liability for crimes committed by high-level perpetrators who exercise control over the actions of the lower-level (fully responsible) perpetrators. Finding the proper mode of liability in these cases is crucial to the International Criminal Court's (ICC) mission of ending impunity for serious international crimes. While international criminal law may be unlikely to deter criminals, especially heads of state and other powerful leaders, it can provide some sense of justice for the victims by convicting and punishing those responsible for their suffering. As such, the functions of international criminal law are to a large extent expressive and retributive. At the same time, it is important to keep the focus of international criminal law on individual responsibility of the perpetrators. It is, therefore, crucial to find proper labels that reflect culpability well. I hope to make a contribution to this search in what follows. This article is divided into five sections. First, I provide a background to the move, recently articulated by the ICC, from the concept of joint criminal enterprise (JCE) to that of indirect perpetration (and indirect co-perpetration) (section 2). Second, I analyse the original presentation of this idea by the German jurist Claus Roxin (section 3). Third, I examine the application of this concept by the German courts, particularly in the 1994 trial of three high level GDR officials held liable as indirect perpetrators for the killings (carried out by the border guards) of refugees at the East/West German border (section 4). Then I present a recent (Winter 2011) proposal by Jens Ohlin to abandon both JCE and indirect perpetration in favour of another mode of collective liability based on joint intentions (section 5). Finally, I defend the concept of indirect perpetration against Ohlin's criticisms, arguing that it offers a more accurate way to label the conduct of high-level perpetrators who carry out crimes by means of direct perpetrators who are themselves liable (section 6).